2001
DOI: 10.1002/ijc.1333
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study of gastric cancer in Venezuela

Abstract: A case-control study to evaluate risk factors for gastric cancer was carried out among 292 cases of gastric cancer and 485 controls in a high-risk area of Venezuela. Subjects were interviewed using a structured questionnaire, which elicited information on residential history, socio-economic status, family history of gastric diseases, smoking, drinking and dietary habits. Habitual diet was estimated from a meal-structured food frequency questionnaire on 75 food items. There was a strong inverse association with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
120
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(131 citation statements)
references
References 25 publications
9
120
1
1
Order By: Relevance
“…This finding is in agreement with 2 casecontrol studies which reported 2.4-3.0 times increase in the risk with dairy product consumption. 17,76 However, this association was not observed in other case-control and cohort studies. The real cause behind this association is not clear, however, this association could be a consequence rather than a cause of the disease, because cases may drink more milk to control symptoms of the disease such as dyspepsia.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This finding is in agreement with 2 casecontrol studies which reported 2.4-3.0 times increase in the risk with dairy product consumption. 17,76 However, this association was not observed in other case-control and cohort studies. The real cause behind this association is not clear, however, this association could be a consequence rather than a cause of the disease, because cases may drink more milk to control symptoms of the disease such as dyspepsia.…”
Section: Discussionmentioning
confidence: 91%
“…Our finding is in agreement with reports of several case-control studies. 17,60,64,65 Prospective study on allium vegetables and GC is limited to a cohort study which reported an inverse association between onion and GC. 66 Moreover, this study did not find any evidence to support a protective role for raw vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…Although BMI is linked with an overall increase in the risk of cancer in general, results from casecontrol studies have indicated, rather, that a low BMI is associated with an increased risk of gastric cancer (7,8,(29)(30)(31), whereas results from prospective studies have yielded contradictory results (3,6,(9)(10)(11)(12)(13)(14)32). The lack of association between overweight or obesity and the risk of noncardia gastric cancer found in our study is in sharp contrast to the strong link that has been established between BMI and gastric cardia and esophageal adenocarcinoma (4-6).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas evidence for a positive association between obesity and risk of gastric cardia cancer has accumulated over recent years (4)(5)(6), epidemiologic findings concerning the relation between body mass index (BMI) and risk of noncardia gastric cancer have been inconsistent (2). There are indications of an inverse association between BMI and noncardia gastric cancer, but prospective studies have been sparse, and there is an obvious risk of bias in studies where mortality data are being used or where weight is reported retrospectively or with too short a latency interval between exposure and the gastric cancer (7)(8)(9)(10)(11)(12)(13)(14). A high physical activity level has been shown to be protective against several cancers, but the small number of investigations of the relation between physical activity and risk of gastric cancer has prevented any firm conclusions from being drawn for this particular tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, epidemiological data on gastric cancer is incomplete in many regions, and non-invasive methods for diagnosing the infection are not widely available. (173) and case-control studies conducted in Asia (188) , Europe (47,61) and Latin America (149) , including Brazil (147) , show that first-degree relatives of gastric cancer carriers have a 2 to 3 times higher risk of developing neoplasia, so search and eventual eradication of bacteria in this population is fully justified. Metachronous tumors in the gastric remnant have been described in up to 10% of patients undergoing gastric, endoscopic or surgical resection for early gastric cancer (182,187,194) .…”
Section: Statement 19mentioning
confidence: 99%